Does “July effect” exist in colonoscopies performed at teaching hospitals? - Desai, Rupak; Patel, Upenkumar; Goyal, Hemant (Translational Gastroenterology and Hepatology, 2018)
Background: To compare the outcomes of the colonoscopies between the early (July–September) and the later (April–June) academic year at the urban-teaching hospitals. Methods: Our study cluster was derived from the National Inpatient Sample (NIS) database for the years 2010–2014. International Classification of Diseases, 9th Revision, Clinical Modification (ICD-9 CM) procedure codes were used to identify the adult patients who underwent inpatient colonoscopy at urban-teaching hospitals. Post-colonoscopy outcomes and the complications were recognized using ICD-9 CM codes among any of the secondary diagnoses. Categorical and continuous variables were assessed using Pearson’s Chi-square and Student’s t-test respectively. Odds of complications during the early vs. later academic year was also evaluated by the two-way hierarchical logistic regression analysis. Results: A total of 124,155 (weighted n=617,907) colonoscopy procedures were performed at the urban teaching hospitals in the US from 2010 to 2014. Out of these, 61,272 (weighted n=304,946) and 62,883 (weighted n=312,961) procedures were performed during early (July to September) and later (April to June) academic months, respectively. There was no significant difference in the all-cause mortality (1.4% vs. 1.4%, P=0.208), and the complications such as colonic perforations (3.1% vs. 3.2%, P=0.229) and postoperative infections (0.6% vs. 0.6%, P=0.733) between the two groups. Similarly, the splenic rupture (0.0% vs. 0.0%, P=0.180) was equally infrequent in both the groups. Bleeding/hematoma following colonoscopy (0.9% vs. 0.8%, P=0.004) was marginally higher during the later academic months. There were no statistically distinctions in terms of length of stay (LOS) (days) (7.3±9.1 vs. 7.3±9.1, P=0.918), total hospitalization charges ($60,549.41 vs. $59,918.56, P=0.311) and discharge of patients to other facilities between the early and the later academic months. Colonoscopy performed during the early academic months was not found to be a significant independent predictor for post-colonoscopy complications such as colon perforation (OR =0.99, 95% CI: 0.93–1.06, P=0.760), postoperative bleeding/hematoma (OR =0.92, 95% CI: 0.81–1.04, P=0.196) and postoperative infection (OR =0.99, 95% CI: 0.84–1.15, P=0.850). Conclusions: There was no “July effect” on the outcomes of colonoscopies between the early vs. the later academic months.